REVOLUTIONS PER MINUTE OR THE PET SHOP BOYS FOREVER - Balfour, Ian (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1991)
The relation of revolution to historical time, the politics of pop music. How the British group The Pet Shop Boys submits pop music, sexuality and politics to an infinitizing rhetoric.